Prepuberal stress and obesity: effects on serum corticosterone, prolactin, testosterone and precancerous prostate lesions in adult rats - Herrera-Covarrubias, D.; Coria-Avila, G.A.; Aranda-Abreu, G.E.; Manzo, J.; Hernández, M.E. (PH Akademperiodyka, 2023)
Summary. Stress during puberty and obesity can represent conditions that facilitate the long-term development of diseases, especially for stress-related disorders that depend on neuroendocrine and immune responses. The prostate is prone to diseases that result from neuroendocrine or immune challenges, such as cancer. Aim: In the present study, we assessed the long-term effects of an acute pubertal stressor (immune-challenge) or obesity on the development of precancerous lesions in rats. Materials and Methods: Pubertal male rats received a single injection of lipopolysaccharide (LPS) or saline during puberty (5 weeks of age). In adulthood (8 weeks old), subgroups of males were fed with hypercaloric liquid diet to induce obesity. This resulted in a total of six subgroups: (1) intact-non obese, (2) intact-obese, (3) saline-non obese, (4) saline-obese, (5) LPS-non obese, and (6) LPS-obese. At 16 weeks of age the rats were sacrified for prostate histology (hematoxylin and eosin stain) and hormone analysis (testosterone, corticosterone and prolactin). Results: As compared to intact-non obese rats, males treated with LPS and those with obesity expressed histological alterations in both the dorsolateral and ventral portions of the prostate. Only prolactin was altered in LPS-treated males, whereas corticosterone was altered in LPS-obese rats. Conclusions: These results indicate that puberal exposure to an immune challenge or obesity facilitate the development of prostatic lesions in adult male rats. We discuss the role of hormones in the development of precancerous lesions.